Molluscan shelltish resources of India - An overview - Narasimham, K A; Kripa, V; Balan, K (Indian Journal of Fisheries, 2011)
In recent times the molluscan shellfish are fast emerging as an important component in the marine fisheries of the country. Cephalopods are much sought after in the export trade. Their production trend is showing spectacular growth rate. The edible oysters, mussels and clams are nutritious sea foods with considerable export potential.